Foreign Labour Migration and Governance in Nepal - Kunwar, Laxman Singh (Journal of Population and Development, 2020)
This paper examines the history and current situation of international foreign labour migration in Nepal. The volume of foreign labour migration in Nepal is in increasing trend. This paper highlights the volumes of absentee population including countries of destinations of labour migrants. The objective of paper is to discuss historical and current aspects of foreign labour migration including governance of labour migration in Nepal. The paper is developed with the help of secondary sources of information and discussed only in Nepalese context in relation with the bilateral, regional and global context. Some major push and pull factors related to foreign labour migration including frequently changing governance acts, policies are also discussed. To govern international foreign labour migration provisions on national, bi-lateral, regional and international level with Nepal’s position are highlighted. The lack of stable and foreign labour friendly migration policies are being unable to address problems of Nepalese migrants properly.